Autoreprezentarea persoanelor cu dizabilități în contextul ghidării în carieră: cazul Republicii Moldova - Cojocaru, Natalia (Calitatea Vieții, 2025)
This article explores the issue of self-advocacy among young people with disabilities in the Republic of Moldova in the context of career guidance. While self-advocacy is internationally recognized as a crucial element in promoting the rights of people with disabilities and facilitating their access to the labor market, in the Republic of Moldova, this concept is relatively new and under-researched. Existing studies in the field of career guidance primarily focus on barriers such as physical and informational accessibility, discriminatory attitudes, and stereotypes toward people with disabilities, with little attention given to self-advocacy. In this context, the article examines the challenges and opportunities for self-advocacy within career guidance, emphasizing the need for its integration into professional orientation processes. The role of self-advocacy in improving employment prospects for people with disabilities is highlighted, as well as the importance of developing appropriate educational and support strategies to enhance their capacity to express and defend their interests in the labor market. The research questions explored in the article include: What are the perceptions of people with disabilities regarding career guidance? What are the main barriers they face in the career guidance process? What role do public institutions, non-governmental organizations, and families play in supporting the self-advocacy of people with disabilities in this context? What are the benefits of career guidance for their self-advocacy? How does self-advocacy influence their access to career guidance opportunities? The article draws upon the findings of the study "Policies and Practices of Career Guidance for Young People with Disabilities in the Republic of Moldova," conducted on a representative national sample comprising 1 111 young people with disabilities, aged between 14 and 35 years. These findings were supplemented with insights from individuals with disabilities who are members of self-advocacy groups, their support persons, and representatives from civil society, collected through qualitative research methods.